Flame propagation in spark ignition engine combustion process using computational fluid dynamics (CFD) - Hanif, Kasmani (2011)
This thesis deals with the flame propagation in spark ignition engine combustion process using Computational Fluid Dynamic (CFD). This study is based on flame propagation inside the combustion chamber which is important as flame propagation affects the engine efficiency, emission and some more. A 3-D model is created based on the Mitsubishi Magma 4G15 that act as a baseline engine. It is then simulated using CFD where its approaches make it a suitable platform to study the internal combustion engine phenomenon. The project simulates only 50o CA starting from the ignition until the completion of the combustion process. The flame radius obtain through simulation is then compared with the experimental data together with the literature review. However, there are discrepancies of the results due to improper boundary condition and inherit limitation of the model. For further simulation of combustion process must consider detail mixture properties, detail boundary condition and model extension for better accuracy data.